(untitled) (Revista de Medicina Clinica, 2023)
Methotrexate is a drug with anti-inflammatory and antineoplastic properties, which has been used in the treatment of dermatological and rheumatological diseases, exerting its function on the inhibition of DNA synthesis. Like all drugs, it can cause toxic adverse effects that can pose a life risk to patients. We present a case of a 61-year-old woman who presented a picture of pulmonary toxicity after the use of the drug, indicated by her underlying rheumatological disease.